Abnormal response of left ventricular systolic function to submaximal exercise in post-partial left ventriculotomy patients - Herdy,A.H. (2007)
Patients with heart failure who have undergone partial left ventriculotomy improve resting left ventricular systolic function, but have limited functional capacity. We studied systolic and diastolic left ventricular function at rest and during submaximal exercise in patients with previous partial left ventriculotomy and in patients with heart failure who had not been operated, matched for maximal and submaximal exercise capacity. Nine patients with heart failure previously submitted to partial left ventriculotomy were compared with 9 patients with heart failure who had not been operated. All patients performed a cardiopulmonary exercise test with measurement of peak oxygen uptake and anaerobic threshold. Radionuclide left ventriculography was performed to analyze ejection fraction and peak filling rate at rest and during exercise at the intensity corresponding to the anaerobic threshold. Groups presented similar exercise capacity evaluated by peak oxygen uptake and at anaerobic threshold. Maximal heart rate was lower in the partial ventriculotomy group compared to the heart failure group (119 ± 20 vs 149 ± 21 bpm; P < 0.05). Ejection fraction at rest was higher in the partial ventriculotomy group as compared to the heart failure group (41 ± 12 vs 32 ± 9%; P < 0.0125); however, ejection fraction increased from rest to anaerobic threshold only in the heart failure group (partial ventriculotomy = 44 ± 17%; P = non-significant vs rest; heart failure = 39 ± 11%; P < 0.0125 vs rest; P < 0.0125 vs change in the partial ventriculotomy group). Peak filling rate was similar at rest and increased similarly in both groups at the anaerobic threshold intensity (partial ventriculotomy = 2.28 ± 0.55 EDV/s; heart failure = 2.52 ± 1.07 EDV/s; P < 0.0125; P > 0.05 vs change in partial ventriculotomy group). The abnormal responses demonstrated here may contribute to the limited exercise capacity of patients with partial left ventriculotomy despite the improvement in resting left ventricular systolic function.